HUBUNGAN LINGKUNGAN PENGENDAPAN FORMASI MALAWA DAN KETERDAPATAN BATUBARA DI DAERAH SOPPENG, SULAWESI SELATAN - Kusnama Kusnama; Syahrir Andi Mangga (Jurnal Geologi dan Sumberdaya Mineral, 2007)
Lithologically, the Malawa Formation comprises medium to coarse-grained quartz sandstone, shale and claystone in the lower part; and mudstone and carbonaceous fine- grained sandstone in the upper part. The thickness of the Malawa Formation in the Gatareng area is about 100 metres. The lower part of the Malawa Formation was deposited in a fluvial environment occupied by terrestrial vegetation such as land algae, fungus, ferns and mangroves, while the upper part of the formation was indicated by fluviatile close to the beach and sand dunes. On the basis of fossil content, the age of the formation is within the range of Middle Eocene -Oligocene.Several coal intercalations which are characteristically black in colour with good luster of sub-bituminous, were found in the formation with the thickness from 50 cm to 120 cm. Based on the lithology succession and the river stream where the coal deposits were found, coal occurred in the Malawa Formation can be divided into two blocks, Bakeko and Kandangsapi Blocks. Each block has some coal seams with different various rock succession.Â Keywords: Malawa Formation, Gatareng Area, sub-bituminous, beach environment